Recovery of Rice Straw Cellulose on Pilot Scale for Fabrication of Aerogel for Oil/Water Separation - Nhi Vo; Chi Thi Xuan Nguyen; Tan M. Le; Co Dang Pham; Nga Hoang Nguyen Do; Kien Anh Le; Thanh Phong Mai; Phung Thi Kim Le (Chemical Engineering Transactions, 2022)
Recently, bio-based materials that are both environmental-friendly and highly functional were synthesized from various waste and biomass. Rice straw, a by-product of paddy production, is abundant lignocellulosic biomass with high cellulose content. The utilization of this natural resource for high functional material often meets with difficulties due to a large amount of lignin and silica present in the material matrix. While rice straw has been employed for biofuel production on pilot scale, its use for cellulose recovery has only been performed in laboratory-scale equipment. Here we show a simple process to effectively recover cellulose from rice straw on a pilot scale, after which the extracted cellulose was used for the preparation of aerogel. The alkali pretreatment removed the majority of lignin and silica, yielding semi-product with cellulose content of 73 %, then the bleaching step with hydrogen peroxide further eliminated colored impurities to increase the cellulose content to 90 %. The obtained cellulose was then employed to fabricate cellulose aerogel with low density, high surface area, and porous structure, which showed a good performance in the separation of oil and water, with the maximum capacity reaching 21.7 g/g. The process is a promising solution for converting rice straw into a more valuable product for water treatment on a larger scale.